(untitled) (CAHIERS MAGELLANES-NS, 2024)
Background: This article discusses level of knowledge and awareness of hepatitis. Due to the prevalence of viral hepatitis, particularly hepatitis B and C, is a significant global health concern. Studies have shown that knowledge and awareness about hepatitis among the general public and healthcare professionals in Saudi Arabia is inadequate. This highlights the need to develop targeted educational programs and preventive healthcare policies to address the knowledge gaps and reduce the burden of viral hepatitis in the country. This study was to determine the level of knowledge and awareness about hepatitis types, symptoms, transmission routes, complications, and risk factors among Saudi populations. Methods: A cross-sectional study in Saudi Arabia evaluated public awareness and knowledge about hepatitis types. Participants were recruited via social media. The inclusion criteria were Saudi residents, while the exclusion criteria were not specified. The sample size was calculated as 384 using the Raosoft calculator, with a 50% indicator percentage, 5% margin of error, and 95% confidence interval. Data was collected through a structured questionnaire and pilot-tested on 20 individuals. The final data was entered into Excel and analyzed using SPSS version 25. This study aims to provide insights into the Saudi population's understanding of hepatitis, which can guide public health interventions. Results: The study assessed the knowledge and awareness of hepatitis among a cohort of 591 participants in Saudi Arabia, revealing critical gaps and areas for improvement. Although a majority (63.3%) identified hepatitis A, B, C, D, and E as viral infections, a significant portion (31.5%) remained uncertain about this fact. While 59.2% recognized personal hygiene as a preventive measure for hepatitis B and C, 25.9% were unsure, indicating a need for better education. Awareness of vaccine availability was also lacking, particularly for hepatitis C, with 47.2% of respondents unaware of any vaccination. Attitudes towards individuals with hepatitis exhibited stigma, as 44% believed such individuals should be barred from certain occupations, while 39.6% expressed concerns about infection rates. Despite a majority (83.6%) acknowledging the importance of blood screening prior to donation, only 18.4% of participants demonstrated high overall knowledge of hepatitis. With 47.9% categorized as having low knowledge and 71.7% displaying only moderate awareness. Conclusion: The study revealed significant gaps in knowledge and awareness of hepatitis types, prevention, and treatment among the Saudi Arabian population. While a majority (63.3%) recognized various hepatitis viruses, a concerning 31.5% remained uncertain about their viral nature. Knowledge of personal hygiene as a preventive measure was noted in 59.2% of the participants. Attitudinal findings revealed a pervasive stigma, with 44% believing individuals with hepatitis should be excluded from certain jobs. Ultimately, only 18.4% displayed high overall knowledge of hepatitis, with 47.9% categorized as having low knowledge levels.